Comparison of Peak Searching Algorithms for Wavelength Demodulation in Fiber Bragg Grating Sensors - Yongqian Li; Yang Xie; Guozhen Yao (2010 2nd International Conference on Information Engineering and Computer Science, 2010)
A wavelength detection system of fiber Bragg grating (FBG) sensors is described. In order to obtain high detection precision and stability, four peak searching algorithms have been analyzed and compared, including differential method, centroid method, cross-correlation method, and Gaussian fitting method. The experimental results show that Gaussian fitting method is suitable for high precision demodulation system, and the maximum measurement error and standard deviation of center wavelength is 5 pm and 0.5 pm, respectively, corresponding to a maximum temperature measurement error and a accuracy of temperature measurement of 0.5 °C and 0.05 °C.